Momentum returns and information uncertainty: Evidence from China - Cheema, Muhammad; Nartea, G. (Elsevier, 2014)
A recent theory of information uncertainty (IU) postulates a negative(positive) relationship between IU and future returns (momentumreturns). We extend this theory by showing that its predictions couldbe conditioned by differences in behavioral biases induced by culture.We find that greater IU does not necessarily result in lower futurereturns in China unlike in the U.S. In fact for some IU proxies, high IUfirms have higher future returns. Second, we confirm earlier evidenceof a weak momentum effect in the Chinese stock market which isconsistent with the low level of individualism among Chinese investorsreported in the literature. Thirdwe find thatmomentumreturns of firmswith greater IU are not necessarily higher than firms with lower IU.